The Sphere of Culture in the System of Strategic Planning of Socio-Economic Development of the Region - S. T. Rumyantseva (Управленческое консультирование)
The cultural sphere is closely connected with the transformations taking place in the society; it is not only their consequence, but also the motivating cause. Today, more than ever, it is important to take this feature into account when developing and implementing state policy. State management and regulation of the economy should be based on value guidelines set by the cultural environment. This should be reflected in a set of measures envisaged by the system of strategic planning of socio-economic development at both the national and regional levels of government. Issues of cultural development require reflection in the main document of strategic planning of the region — the strategy of socio-economic development of the constituent entity of the Russian Federation. The structure of regional strategies is not strictly regulated. This document is formed taking into account local specifics and reflects the existing problems of economic and social development. When developing regional strategies, it is important to  include a section devoted to the development of the cultural sphere as a factor influencing the development of other components of the regional economy.